Effects of Sex and Mild Intrainsult Hypothermia on Neuropathology and Neural Reorganization following Neonatal Hypoxic Ischemic Brain Injury in Rats. (3rd March 2016) - Smith, Amanda L.; Rosenkrantz, Ted S.; Fitch, R. Holly
Abstract : Hypoxia ischemia (HI) is a recognized risk factor among late-preterm infants, with HI events leading to varied neuropathology and cognitive/behavioral deficits. Studies suggest a sex difference in the incidence of HI and in the severity of subsequent behavioral deficits (with better outcomes in females). Mechanisms of a female advantage remain unknown but could involve sex-specific patterns of compensation to injury. Neuroprotective hypothermia is also used to ameliorate HI damage and attenuate behavioral deficits. Though currently prescribed only for HI in term infants, cooling has potential intrainsult applications to high-risk late-preterm infants as well. To address this important clinical issue, we conducted a study using male and female rats with a postnatal (P) day 7 HI injury induced under normothermic and hypothermic conditions. The current study reports patterns of neuropathology evident in postmortem tissue. Results showed a potent benefit of intrainsult hypothermia that was comparable for both sexes. Findings also show surprisingly different patterns of compensation in the contralateral hemisphere, with increases in hippocampal thickness in HI females contrasting reduced thickness in HI males. Findings provide a framework for future research to compare and contrast mechanisms of neuroprotection and postinjury plasticity in both sexes following a late-preterm HI insult.